The helium flux from the continents and ubiquity of low-3He/4He recycled crust and lithosphere. (15th March 2015) - Day, James M.D.; Barry, Peter H.; Hilton, David R.; Burgess, Ray; Pearson, D. Graham; Taylor, Lawrence A.
Highlights: First helium isotope results for recycled oceanic protoliths (eclogites, pyroxenites). First combined helium isotope and trace-element abundance data for cratonic peridotites. Hypothesis to reconcile terrestrial helium flux from the continents. Continental lithospheric mantle and recycled oceanic crust are low- 3 He/ 4 He sources for intraplate magmas. Abstract: New helium isotope and trace-element abundance data are reported for pyroxenites and eclogites from South Africa, Siberia, and the Beni Bousera Massif, Morocco that are widely interpreted to form from recycled oceanic crustal protoliths. The first He isotope data are also presented for Archaean peridotites from the Kaapvaal (South Africa), Slave (Canada), and Siberian cratons, along with recently emplaced off-craton peridotite xenoliths from Kilbourne Hole, San Carlos (USA) and Vitim (Siberia), to complement existing 3 He/ 4 He values obtained for continental and oceanic peridotites. Helium isotope compositions of peridotite xenoliths vary from 7.3 to 9.6 RA in recently (<10 kyr) emplaced xenoliths, to 0.05 RA in olivine from cratonic peridotite xenoliths of the 1179 Ma Premier kimberlite, South Africa. The helium isotope compositions of the peridotites can be explained through progressive sampling of 4 He produced from radiogenic decay of U and Th in the mineral lattice in the older emplaced peridotite xenoliths. Ingrowth of 4 He is consistent with generally higher 4 He concentrations measured in olivine from older emplaced peridotite xenoliths relative to those from younger peridotite xenoliths. Collectively, the new data are consistent with pervasive open-system behaviour of He in peridotite xenoliths from cratons, mobile belts and tectonically-active regions. However, there is probable bias in the estimate of the helium isotope composition of the continental lithospheric mantle (6.1 ± 2.1 RA ), since previously published databases were largely derived from peridotite xenoliths from non-cratonic lithosphere, or phenocrysts/xenocrysts obtained within continental intraplate alkaline volcanics that contain a contribution from asthenospheric sources. Using the new He isotope data for cratonic peridotites and assuming that significant portions (>50%) of the Archaean and Proterozoic continental lithospheric mantle are stable and unaffected by melt or fluid infiltration on geological timescales (>0.1 Ga), and that U and Th contents vary between cratonic lithosphere and non-cratonic lithosphere, calculations yield a 3 He flux of 0.25–2.2 atoms/s/cm 2 for the continental lithospheric mantle. These estimates differ by a factor of ten from non-cratonic lithospheric mantle and are closer to the observed 3 He flux from the continents (<1 atoms/s/cm 2 ). Pyroxenites and eclogites from the continental regions are all characterized by 3 He/ 4 He (0.03–5.6 RA ) less than the depleted upper mantle, and relatively high U and Th contents. Together with oceanic and continental lithospheric peridotites, these materials represent reservoirs with low time-integrated 3 He/(U + Th) in the mantle. Pyroxenites and eclogites are also characterized by higher Fe/Mg, more radiogenic Os–Pb isotope compositions, and more variable δ 18 O values (∼3‰ to 7‰), compared with peridotitic mantle. These xenoliths are widely interpreted to be the metamorphic/metasomatic equivalents of recycled oceanic crustal protoliths. The low- 3 He/ 4 He values of these reservoirs and their distinctive compositions make them probable end-members to explain the compositions of some low- 3 He/ 4 He OIB, and provide an explanation for the low- 3 He/ 4 He measured in most HIMU lavas. Continental lithospheric mantle and recycled oceanic crust protoliths are not reservoirs for high- 3 He/ 4 He and so alternative, volumetrically significant, He-rich reservoirs, such as less-degassed (lower?) mantle, are required to explain high- 3 He/ 4 He signatures measured in some intraplate lavas. Recycling of oceanic crust represents a fundamental process for the generation of radiogenic noble gases in the mantle, and can therefore be used effectively as tracers for volatile recycling.